Development of a Web-Based Educational Information System Using the RAD Method: A Case Study at Persahabatan Hospital - Reza Setiawan; Veri Arinal (International Journal Software Engineering and Computer Science (IJSECS), 2025)
RSUP Persahabatan operates as a teaching hospital supporting clinical education for medical professionals through Specialist Medical Education Programs (PPDS) and medical internships (Coass). The current registration infrastructure exhibits significant operational deficiencies, including recurring data entry errors, compromised information integrity, and dependence on manual reporting via Microsoft Excel. These limitations create administrative bottlenecks and reduce process reliability. To address these challenges, we developed a web-based student registration platform employing the Rapid Application Development (RAD) methodology. RAD facilitates accelerated development cycles through iterative prototyping and continuous stakeholder engagement. The platform incorporates automated document validation mechanisms and WhatsApp notification systems triggered upon registration approval. Implementation involved four RAD phases: planning, user design, construction, and cutover. Black-box testing and user acceptance testing validated functional integrity across all modules. Testing results demonstrated zero errors in registration workflows, document uploads, and verification processes. The platform achieved a maximum response time of 2.8 seconds per transaction while supporting concurrent user access. Results indicate measurable improvements in administrative efficiency, data accuracy, and processing speed compared to the previous manual system.